Review of Imaging Techniques for Analysis in Medical and Industrial Field - Soojey Deshpande, Sneha Salvekar, Swati Joshi, Sharad Jagtap (Mathematical Statistician and Engineering Applications, 2022)
This is a review paper which shows a descriptive comparison of the technologies available for imaging and its various applications in industrial and medical fields. Since tomography is highly used for imaging and fault finding it has been given greater interest by researchers in these fields. For medical applications some in cases it is highly crucial about adapting a specific technique for diagnosis and cure of certain faults in human body. There are different technologies available for imaging and fault finding variably used in either or both industrial and medical fields such as, Computed Tomography, Microwave Tomography, Electromagnetic Induction Tomography, Radiography, Electrical Capacitance Tomography, Electrical Resistance Tomography and Ultra Sound Tomography. All these may not be applicable for one type of fault finding simultaneously but are applicable for at least one or two types of faults in either of the fields. After reading this paper one may get a clear picture of opting and enhancing over a specific type of imaging techniques according to their requirement.